Sex modifies the predictive value of computed tomography combined with serum potassium for primary aldosteronism subtype diagnosis - Wu, Yingxing; Wu, Zuxiang; Rao, Jingan; Hu, Huan; Chen, Zhiqiang; Hu, Chenkai; Peng, Qiang; Li, Ping (Frontiers in Endocrinology, 2023)
We aimed to investigate the predictive value of the CT findings combined with serum potassium levels for primary aldosteronism (PA) subtype diagnosis, with a particular interest in sex differences.In this retrospective study, 482 PA patients who underwent successful adrenal venous sampling (AVS) and had available data were eventually included. The subjects were diagnosed as having either unilateral (n = 289) or bilateral PA (n = 193) based on AVS. We analyze the concordance rate between AVS and adrenal CT combined with serum potassium and performed a logistic regression analysis to assess the prevalence of unilateral PA on AVS.The total diagnostic concordant rate between CT findings and AVS was 51.5% (248/482). The prevalence of hypokalemia in males and females was 47.96% (129/269) and 40.85% (87/213), respectively. The occurrence of unilateral lesion on CT and hypokalemia are significantly associated with an increased prevalence of unilateral PA [odds ratio (OR) 1.537; 95% confidential interval (CI) 1.364-1.731; P 2 <0.001]. In male participants, G2 (bilateral lesion on CT and normokalemia), G3 (unilateral lesion on CT and normokalemia), G4 (bilateral normal on CT and hypokalemia), G5 (bilateral lesion on CT and hypokalemia), and G6 (unilateral lesion on CT and hypokalemia) were significantly increased for prevalence of unilateral PA